The Effect of Creativity Skill, Motivation, Locus of Control on Self-Efficiency That Impact on the Success of Culinary Tourism Entrepreneurs in North Sumatra - SEMBIRING, Rasmulia; LUBIS, Umi Yusniar; SYAIFUDDIN, Syaifuddin (Journal of Environmental Management and Tourism, 2023)
The purpose of this study is to obtain an overview of the variables creativity skills , motivation, locus of control affects the variables of increasing the success of culinary entrepreneurs in North Sumatra through the moderating variable of self-efficacy. In this study, the existing variables are closely related to things that affect the success of entrepreneurs such as creativity skills, motivation, locus of control and self-efficacy as moderating variables, thus influencing the dependent variable, namely increasing entrepreneurial success in running a culinary business in North Sumatra. The research method used in this research is descriptive quantitative research method using path analysis. In this study, the independent variables are related to factors that affect the success of culinary entrepreneurs such as creativity skills, motivation, locus of control and affect the moderating efficacy variables that connect the dependent and independent variables, while the dependent variable is to increase entrepreneurial success in running a culinary business in North Sumatra. , data analysis using AMOS 18 and data taken from data on the number of culinary entrepreneurs in North Sumatra in 2016-2020. Partially, the productivity skill, motivation and locus of control variables have a significant effect on the self-efficacy variable and have a significant effect on the variable increasing the success of culinary entrepreneurs in North Sumatra, while simultaneously the productivity skill, motivation and locus of control variables have an indirect significant effect on the increasing variable the success of culinary entrepreneurs in North Sumatra through self-efficacy variables. Based on the results of the research analysis, the conclusion that can be drawn is that partially productivity skill, motivation and locus of control variables have a significant effect on self-efficacy variables and have a significant effect on variables increasing the success of culinary entrepreneurs in North Sumatra, while simultaneously the productivity skills, motivation and locus of control indirectly has a significant effect on the variable increasing the success of culinary entrepreneurs in North Sumatra through self-efficacy variables.Through the results of research that has been stated that the Productivity skill variable possessed by an entrepreneur in the culinary field in North Sumatra must be able to increase the creative abilities possessed in increasing the innovation of their culinary products by creating a new product or modifying it will be able to increase the motivation of a person.